Caught in the trap? The disincentive effect of social assistance - Olivier Bargain; Karina Doorley (University College Dublin, UCD School of Economics, 2009)
While financial incentives usually have a significant effect on the labor supply of married women and single mothers, the evidence about the participation elasticity of childless singles, and single males especially, is more scant. This is, however, important in countries like France and Germany, where single individuals constitute the core of social assistance recipients. As yet, there is no conclusive evidence about whether, and to what extent, this group is affected by the financial disincentives embedded in the generous redistributive programs in place in these countries. In this paper, we exploit a particular feature of the main welfare scheme in France (Revenu Minimum d'Insertion, RMI), namely that childless adults under age 25 are not eligible for it. Using a regression discontinuity approach and the French micro-census data, we find that the RMI reduces the employment of uneducated single men by 7% - 10%. Important policy implications are drawn.
hdl:10197/2603
Keywords: H52; J21; 330; Regression discontinuity; Welfare; Social assistance; Labor supply